Gestión del riesgo crediticio de la Cooperativa de Ahorro y Crédito educadores de Cotopaxi "Cacec" ltda., ubicada en la ciudad Latacunga, provincia Cotopaxi en el período del 1 de enero al 31 de diciembre 2014 - Nauta Padilla, Luis Daniel (2016)
This research was conducted at the Cooperativa de Ahorro y Crédito Educadores de Cotopaxi “CACEC” Ltda., with the aim of applying a Credit Risk Management to measure the level of risk exposure and scope of objectives and targets, for this purpose the inductive, analytical, observational, descriptive method was used, techniques are also applied as the interview conducted the manager and employee surveys and members of the organization, which served as support for the collection of information, in order to meet the actual situation. In the cooperative Credit Risk Management applied in the January 1 to December 31 period, 2014….